There’s an elephant in the archive! Two 20th-century reports of Pleistocene remains in the Rome area - Altamura, Flavio (Journal of Mediterranean Earth Sciences, 2023)
Two archival finds recounting the discovery of Pleistocene elephant remains in the Rome area are presented and analyzed. The first consists of two newspaper clippings kept in Filippo Passamonti’s archive (now in the Monastic Archives of the Abbey of Grottaferrata); dated 1934, they report the finding of a “mammoth” skeleton in the Valle Marciana (a maar formed during the last hydromagmatic phase of the Latium volcano), near the town of Grottaferrata. The second is a letter sent to Alberto Carlo Blanc in 1959 and found in his personal archive; it relates the discovery of the remains of Pleistocene elephants in the Fosso Sant’Agnese area in Rome, along the present-day course of the Aniene river, not far from the other known fossil deposits of Saccopastore and Sedia del Diavolo. In this paper, these archival items are put into topographic, historical, geological and archaeological context, adding new elements to our knowledge of the presence of paleontological remains in the Roman Campagna.